Conceptual Metaphor as a Means of Persuasion in Indonesian President Prabowo Subianto's Speech - Ksatria, Aldo (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2024)
The objectives of this research are to find conceptual metaphors and their persuasive functions employed by Indonesian President Prabowo Subianto on his speech at the Shangri-La Dialogue 2024. This research utilizes a qualitative descriptive method, grounded in the conceptual metaphor theory (CMT) by Lakoff and Johnson (1980) and the categories of persuasive purposes of metaphors as outlined by Charteris-Black (2018). The research found three types of conceptual metaphors: Important is Depth (orientational metaphor), strategies are tools (ontological metaphor), and trust is a financial asset (structural metaphor). These metaphors serve various persuasive functions, including ideological, empathetic, predicative, and heuristic purposes. The findings may be valuable for those interested in using conceptual metaphors as persuasive tools to engage and influence their audiences.